The state of effective use of micro-prismatic optical structures for the treatment of children strabismus in Ukraine - Солоніна, Н. В.; Бутенко, Л. В.; Гайдамакін, О. В.; Олійник, Д. Є.; Возненко, В. В. (Інститут проблем реєстрації інформації НАН України, 2021)
Strabismus is an eye disease of children. The classic method of treating strabismus is diagnosis, conservative and surgical treatment. Linear two-dimensional micro-prismatic structures created at the Institute of Information Registration Problems of the National Academy of Sciences of Ukraine made it possible to use them in ophthalmology to measure strabismus angles. An important achievement was the creation of special optical micro prisms. In 2009, unique prism-spherical-cylindrical lenses were created for non-surgical treatment of strabismus and postoperative rehabilitation of patients. The production of medical glasses with these lenses is also set up. The glasses are light and easy to use, have the effect of prolonged orthoptodiplotics and do not require additional hardware treatment. The manufacturer receives doctor's prescriptions directly from patients, via the Internet, fax or mail. The Institute of Problems of Information Registration of the National Academy of Sciences of Ukraine has created an information resource (fren.com.ua) for the needs of consumers and doctors regarding the treatment of strabismus. This site is made for taking into account the use of mobile devices: tablets and mobile phones. Our 10 years experience in the use of eye-glasses with unique prism-spherical-cylindrical lenses in the treatment of strabismus in children is analyzed. Micro-prismatic eye-glasses reduce the treatment time and help to accurately calculate the angle of strabismus, respectively, to make an accurate surgical treatment. Numerous studies have shown that the method of using the micro-prismatic technologies is effective in the treatment of children aged about 2–3 years. The annual analysis of diagnosis and treatment with micro-prism eye-glasses showed a steady increase in orders for such eye-glasses and the expansion of the range of doctors who have mastered this latest technology. These doctors successfully apply the provided technology in their practice. Given the high efficiency of prism-spherical-cylindrical glasses, it is necessary to expand their implementation in all regions of Ukraine. Tabl.: 1. Fig.: 5. Refs: 9 titles.